Attitudes towards Communicative Language Teaching: The Case of EFL Learners and Teachers - Khatib, Mohammad; Ashoori Tootkaboni, Arezoo (Íkala, Revista de Lenguaje y Cultura, 2019)
Although in recent years a great number of studies have been conducted on the use of communicative language teaching (clt) in English as a foreign language (efl) settings, relatively few have specifically dealt with comparing and con-trasting the foreign language teacher’s beliefs with those of their own students concerning the clt approach. Hence, this study was designed to delve into teach-ers’ beliefs and learners’ beliefs regarding six main tenets of the communicative approach within the efl context of Iran. To this end, a Likert-type attitude scale was developed and administered to 154 teachers and 242 learners of English. The results revealed that although both groups of participants held favorable attitudes toward clt, teacher participants had significantly higher levels of perception regarding clt tenets in terms of the role of grammar, the learner’s role, the teach-er’s role, and error correction/evaluation. However, no significant differences were found between language learners and teachers concerning group/pair work and native language role. The participants’ favorable attitudes were taken to indi-cate positive signals for the implementation of clt in the Iranian context because its core tenets seem to be welcomed in the context of this study.